Perkembangan sosial dan emosional pada anak usia dini - Hasanah, Aisya Uswatun (Maliki Interdisciplinary Journal, 2025)
The socio-emotional aspect plays a crucial role in early childhood development, as it helps children learn to manage emotions, build relationships, and develop empathy. However, in practice, many children still face difficulties in expressing feelings, collaborating with peers, and establishing positive social interactions. This article aims to describe creative learning strategies that can enhance the socio-emotional abilities of early childhood. The study employed a qualitative approach using library research by reviewing relevant literature. The findings reveal that creative strategies such as role play, singing, collaborative games, and Islamic storytelling effectively foster social skills, self-confidence, and empathy in children. In conclusion, the implementation of creative learning strategies is proven to be beneficial in early childhood education and can serve as an alternative approach for teachers and parents